2010
DOI: 10.1519/jsc.0b013e3181bf3bb0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ballistic and Static Stretching on Hamstring Muscle Length Using an Equal Stretching Dose

Abstract: The purpose of this investigation was to determine which stretching technique, static or ballistic, is most effective for increasing hamstring muscle length when delivered at the same stretching dose over a 4-week training program. A single-blind, randomized controlled trial design was used in this investigation. Thirty-two participants (16 women and 16 men) between the ages of 18 and 27 years participated in the study. All participants who had a pre-training knee extension angle of less than 20° were excluded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 29 publications
1
11
1
Order By: Relevance
“…This result suggests that a 4-week SS training program is effective for increasing ROM, which is consistent with previous studies (Chan et al 2001;Covert et al 2010;Gajdosik 1991Gajdosik , 2001Marques et al 2009;Reid and McNair 2004;Santonja Medina et al 2007). Animal studies showed that the number of sarcomeres in a series of muscles can be changed by prolonged immobilization in (Goldspin et al 1974;Tabary et al 1972;Williams and Goldspink 1978), leading to speculation that increases of maximum ROM may be related to increases in the number of sarcomeres in series, and a concurrent increase in length of the stretched muscles (Chan et al 2001;Gajdosik 1991Gajdosik , 2001Reid and McNair 2004).…”
Section: The Change In Mtu After Ss Training Programsupporting
confidence: 92%
See 1 more Smart Citation
“…This result suggests that a 4-week SS training program is effective for increasing ROM, which is consistent with previous studies (Chan et al 2001;Covert et al 2010;Gajdosik 1991Gajdosik , 2001Marques et al 2009;Reid and McNair 2004;Santonja Medina et al 2007). Animal studies showed that the number of sarcomeres in a series of muscles can be changed by prolonged immobilization in (Goldspin et al 1974;Tabary et al 1972;Williams and Goldspink 1978), leading to speculation that increases of maximum ROM may be related to increases in the number of sarcomeres in series, and a concurrent increase in length of the stretched muscles (Chan et al 2001;Gajdosik 1991Gajdosik , 2001Reid and McNair 2004).…”
Section: The Change In Mtu After Ss Training Programsupporting
confidence: 92%
“…There have been many studies about the effects of SS training programs (Chan et al 2001;Covert et al 2010;Gajdosik 1991Gajdosik , 2001Marques et al 2009;Reid and McNair 2004;Santonja Medina et al 2007), and in these studies SS training programs were shown to have increased the maximum range of motion (ROM). However, the measurement of maximum ROM has a number of limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Some examples would include the ability of a goaltender in ice hockey to maximally abduct his/her legs when in a butterfly position, gymnasts performing and holding a split position, wrestling, martial arts, synchronized swimming, figure skating and others. Although some studies have indicated that dynamic stretching provides similar increases in static flexibility as static stretching (Beedle and Mann 2007), other studies have indicated that dynamic stretching is not as effective at increasing static flexibility as static stretching within a single warm-up session (Bandy et al 1998;O'Sullivan et al 2009) or with prolonged training (Covert et al 2010). Hence, it could be important to include static stretching in the warm-up for specific sport flexibility applications.…”
Section: Effect Of Stretching Durationmentioning
confidence: 99%
“…For example, Covert et al (Covert et al, 2010) found that increases in hamstring flexibility were significantly higher with four weeks of static stretching (11.9°) when compared to 4-weeks ballistic stretching (3.8°). In contrast, LaRoche and Connolly (2006) found that four weeks of static stretching (8.6°) did not significantly differ from 4-weeks of ballistic stretching (9.7°).…”
Section: Effects Of Dynamic and Standard Stretching On Flexibilitymentioning
confidence: 99%